Rice Husk Filled Polymer Composites - Reza Arjmandi; Azman Hassan; Khaliq Majeed; Zainoha Zakaria (International Journal of Polymer Science)
Natural fibers from agricultural wastes are finding their importance in the polymer industry due to the many advantages such as their light weight, low cost and being environmentally friendly. Rice husk (RH) is a natural sheath that forms around rice grains during their growth. As a type of natural fiber obtained from agroindustrial waste, RH can be used as filler in composites materials in various polymer matrices. This review paper is aimed at highlighting previous works of RH filled polymer composites to provide information for applications and further research in this area. Based on the information gathered, application of RH filled composites as alternative materials in building and construction is highly plausible with both light weight and low cost being their main driving forces. However, further investigations on physical and chemical treatment to further improve the interfacial adhesion with polymeric matrix are needed as fiber-polymer interaction is crucial in determining the final composite properties. Better understanding on how the used polymer blends as the matrix and secondary fillers may affect the properties would provide interesting areas to be explored.